Green innovation risk index screening under the global value chain based on the group decision characteristic root method - Sun, Yingying (Frontiers in Environmental Science, 2023)
Due to the large number of factors affecting the risk of green innovation under the global value chain, the screening of risk indicators is a key link in developing green innovation activities.Through the analysis of the influencing factors of the current green innovation risk, the primary index of green innovation risk is established. The group decision characteristic root method is used to identify the key importance of primary indicators of green innovation risk and construct the global value chain's green innovation risk index system, which provides a scientific method and new ideas for measuring and evaluating green innovation risk in the global value chain.